Evaluation of the Fun FRIENDS program with a sample of Mexican children - Gallegos Guajardo, Julia; Ruvalcalba Romero, Norma A.; Chávez Amavizca, Ania; Barrett, Paula (Pensando Psicología, 2020)
Introduction: Anxiety symptoms in young children can have negative consequences such as the deterioration of family and interpersonal functioning, and may lead to the development of an anxiety disorder; therefore, the importance of prevention.Objective: The aim of this study was to evaluate the effectiveness of the Fun FRIENDS program in the reduction of children’s anxiety symptoms and the promotion of emotional and behavioral competences as a protective factor in a sample of Mexican children.Methodology: The participants included 49 children from the first grade at elementary school along with their teachers. The program was implemented by teachers as twelve consecutive one-week sessions conducted in the classroom. The outcome was measured with a pretest-posttest quasi-experimental design. Measures included the Preschool Anxiety Scale (PAS), for parents, Behavioral and Emotional Rating Scale (BERS-2), for parents, and Strengths and Difficulties Questionnaire (SDQ), for parents and teachers.Results: Findings showed a decrease in the subscale of separation anxiety of the PAS, an increase in the interpersonal, intrapersonal and affective strengths subscales of the BERS-2, and an increase in prosocial behavior as measured by the SDQ.Conclusions: Results indicate promise for the effectiveness of the Fun FRIENDS program as an early intervention program based on the promotion of resilience for Mexican children.
Keywords: anxiety; children; prevention; resilence; Fun FRIENDS